2023
DOI: 10.3389/fimmu.2023.1133207
|View full text |Cite
|
Sign up to set email alerts
|

Imaging assessment of toxicity related to immune checkpoint inhibitors

Abstract: In recent years, a wide range of cancer immunotherapies have been developed and have become increasingly important in cancer treatment across multiple oncologic diseases. In particular, immune checkpoint inhibitors (ICIs) offer promising options to improve patient outcomes. However, a major limitation of these treatments consists in the development of immune-related adverse events (irAEs) occurring in potentially any organ system and affecting up to 76% of the patients. The most frequent toxicities involve the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 162 publications
0
14
0
Order By: Relevance
“…A few studies linked the high splenic-to-liver ratio on PET/CT to splenic irAEs, notably with ipilimumab in metastatic melanoma [7,71,72]. However, splenic irAEs are relatively rare, and splenic uptake is more often regarded as a surrogate of immune On some rare occasions, adrenalitis occurs as an irAE; on PET, it is mainly seen as increased FDG uptake; when turning into a chronic phase, it may be seen as bilateral atrophy of the glands [69].…”
Section: Splenitismentioning
confidence: 99%
See 3 more Smart Citations
“…A few studies linked the high splenic-to-liver ratio on PET/CT to splenic irAEs, notably with ipilimumab in metastatic melanoma [7,71,72]. However, splenic irAEs are relatively rare, and splenic uptake is more often regarded as a surrogate of immune On some rare occasions, adrenalitis occurs as an irAE; on PET, it is mainly seen as increased FDG uptake; when turning into a chronic phase, it may be seen as bilateral atrophy of the glands [69].…”
Section: Splenitismentioning
confidence: 99%
“…Pneumonitis is a rare but sometimes lethal irAE following ICIs. It is even the most lethal irAE with anti-PD-1/PD-L1 drugs, being the cause of ~35% of immunotherapyrelated deaths (~1% of deaths by CTLA-4 inhibitors), making it sometimes necessary to discontinue treatment [7,29,79,80]. Nishino et al (2016) found that the median onset time of pneumonitis was 2.6 months after immunotherapy initiation [81].…”
Section: Pneumonitismentioning
confidence: 99%
See 2 more Smart Citations
“…Currently, the efficacy and adverse events of tumor immunotherapy can be preliminarily assessed through imaging studies. [9][10][11] It is also possible to establish image-based biomarkers 12,13 or efficacy prediction models combined with clinical characteristics to screen the appropriate population for immunotherapy and implement personalized treatment. 14,15 Clinically, it is routine to use various medical image-based efficacy evaluation standards for solid tumors to assess treatment efficacy.…”
Section: Introductionmentioning
confidence: 99%